Survei Golongan Darah Dan Tingkat Daya Tahan Kardiovaskuler Pada Atlet Futsal - Ahmad Rusdi; Didin Tohidin; Arif Fadli Muchlis; Hadi Pery Fajri (JURNAL STAMINA, 2022)
The problem found by researchers is to find out the blood type of each futsal athlete. This type of research is descriptive research that aims to provide accurate data about blood type and cardiovascular endurance. The sample of this study amounted to 15 people. The sampling technique used was total sampling. Data collection is carried out so that later it can describe a situation that will later be displayed to test the truth of the data obtained. The research instrument used the slide and bleep test methods. The data analysis technique that the researcher uses is a histogram graph with percentage calculations. Based on the results of the data obtained from the slide method, there were 5 athletes with blood group A, 5 athletes with blood group B, 5 athletes with blood group AB, and 5 athletes with blood group O. The results of cardiovascular endurance were obtained by means of the bleep test, as many as 15 people who took part obtained very good categories (>51,6) as many as 7 people with a percentage of 47%, good category (42,6-51.5) as many as 4 people with a percentage of 27%, moderate category (33.8-42.5) as many as 4 people with 27% and none in the less and less category